Analisis Determinan Penyerapan Tenaga Kerja UMKM di Indonesia: Peran PDB UMKM, Suku Bunga, dan Upah Minimum - Hardimanto, Zana Zein; Azzahra, Rahmadani Syafiah; Maharani Ramadhan, Nova Adisti; Amalina, Farida Nur (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to investigate how interest rates (BI Rate), national average minimum wages, and Gross Domestic Product (GDP) of MSMEs affect labor absorption in the Micro, Small, and Medium Enterprises (MSMEs) sector in Indonesia during the period 2018–2023. This study uses panel data from 38 provinces in Indonesia used to use multiple linear regression analysis with quantitative methods. The results of the study indicate that MSME GDP has a positive and significant effect on labor absorption, which means that economic growth in the MSME sector can encourage more jobs. Conversely, minimum wages have a negative and significant effect on labor absorption, which means that an increase in minimum wages can reduce the ability of MSMEs to recruit workers. The results of the analysis show that although interest rates have a negative effect, it is small. The high R-square value (99.74) indicates that the regression model used can well explain variations in labor absorption. These results provide policymakers with important insights to create policies that support MSME growth and create sustainable jobs by considering the relationship between GDP and minimum wages.